Analisis Faktor-faktor Pelayanan Trans Jogja Berdasarkan Persepsi Pengguna Sepeda Motor - Septiana, Ade Primerita; Priyanto, Sigit; Dewanti, Dewanti (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2023)
In 2021, the population of motorized vehicles in DIY reached 3 million units of which 85% were motorcycles. The growth in the number of motorized vehicles results in increased congestion, pollution, and traffic accidents. To overcome transportation problems in Yogyakarta, in 2008 the government operated BRT (Bus Rapid Transit) based public transportation, Trans Jogja. However, various studies have shown that the load factor of Trans Jogja is very low. This study was conducted to see the characteristics of motorcyclist and latent factors of public transportation services that are prioritized by motorcycle users to switch modes to Trans Jogja. Primary data was obtained online and offline from 455 motorcycle users by answering a research questionnaire consisting of four sections, namely sociodemographic characteristics, travel characteristics and service factors that are prioritized to switch to Trans Jogja. Data analysis was conducted using descriptive methods, crosstab and factor analysis with SPSS. The results of the crosstab analysis show that the sociodemographic characteristics of respondents that correlate with the number of motorcycle ownership are age, income, pocket money, number of family members.Based on the factor analysis of public transport services prioritized by motorcycle users to switch to Trans Jogja, 4 latent factors were obtained, namely Trans Jogja service performance, transit experience, bus facilities and fees and parking. Keywords: Motorcycle, Trans Jogja, mode shift, factor analysis